Spatiotemporal analysis of buildings in flood hazard areas in Guarapuava, Paraná, Brazil - Redin Vestena, Leandro; Ap. Almeida dos Santos, Rebeka; Eurich Machado, Fabiula; Frajuca Lopes, Jaime Sergio Frajuca Lopes (Geografares, 2024)
Rapid urbanization and climate emergencies pose significant challenges to urban planning, management, monitoring, and the regulation of inadequate land occupations, particularly in flood-prone areas. This study aims to investigate the spatiotemporal dynamics of land use and occupation in critical flood hazard zones in Guarapuava (PR) from April to November 2023. The methodological approach involved visual interpretation of Google Earth imagery and orthomosaics obtained through unmanned aerial vehicles (UAVs), focusing on areas requiring public attention. The results indicate an increase in soil impermeabilization and a growing number of residential structures in flood-hazard areas. The findings suggest that the pace of urban occupation in flood-prone zones often exceeds regulatory agencies’ monitoring and enforcement capacity. Therefore, beyond implementing land use regulations in flood hazard areas, effective enforcement measures are crucial, as greater exposure to hazards heightens the risk of disasters.